A kind of phosphogypsum concrete and preparation method thereof

By pretreating phosphogypsum and subsequent mixed granulation and firing process, light phosphogypsum aggregates with high strength and good permeability are prepared, which solves the problems of low strength and poor durability of phosphogypsum concrete, and achieves concrete performance matching with natural river sand.

CN118894664BActive Publication Date: 2025-03-18KUNMING UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410934492.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-12
Publication Date
2025-03-18
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

Phosphogypsum concrete has low strength and poor durability, making it difficult to effectively replace natural sand and gravel, resulting in environmental pollution and waste of resources.

Method used

By pretreating phosphogypsum, including drying, crushing and calcining, removing impurities, and then mixing with gelling materials, alkali triggers, retarders and water, ball milling, granulating, curing and firing, a light aggregate of phosphogypsum with good strength and permeability is produced.

Benefits of technology

The density and performance of phosphogypsum light aggregate is improved, so that it can replace natural river sand. The obtained phosphogypsum concrete has high strength and good durability, and its performance is not inferior to that of concrete prepared by natural river sand as aggregate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004940874520000061
    Figure BDA0004940874520000061
Patent Text Reader

Abstract

The invention discloses a phosphogypsum concrete and a preparation method thereof, and belongs to the technical field of building materials. Using phosphogypsum as a raw material, a phosphogypsum lightweight aggregate with high strength and good chemical resistance is prepared through a unique preparation process, and the phosphogypsum concrete prepared with the phosphogypsum as a raw material is not inferior to the concrete prepared with natural river sand as a raw material in terms of strength and durability. The phosphogypsum concrete provided by the invention is economical and environmentally friendly, and can not only realize the high-value utilization of phosphogypsum waste, but also reduce the use of natural river sand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to phosphogypsum concrete and a preparation method thereof. Background Art

[0002] Phosphogypsum is a solid waste produced in the wet phosphoric acid process, and its main component is calcium sulfate dihydrate. The composition of phosphogypsum is relatively complex. In addition to calcium sulfate, there are also incompletely decomposed phosphate ore, residual phosphoric acid, fluoride, acid insoluble matter, organic matter, etc. Among them, the presence of fluorine and organic matter has the greatest impact on the resource utilization of phosphogypsum. The random discharge and accumulation of phosphogypsum has seriously damaged the ecological environment, not only polluting groundwater resources, but also causing waste of land resources.

[0003] Natural sand and gravel are important components of concrete materials. However, as non-recyclable natural resources, large-scale development of sand and gravel will inevitably cause problems such as environmental degradation and energy consumption. Therefore, it is necessary to consider replacing these natural resources with a low-value-added product.

[0004] Currently, there are technical solutions for using phosphogypsum to prepare aggregates to replace natural sand and gravel. However, there are still problems such as the low strength of the prepared phosphogypsum aggregate and the poor durability of the phosphogypsum concrete prepared with it. How to improve the preparation process of phosphogypsum aggregate to enhance the performance of concrete prepared with it as raw material is a new direction to be studied in this field. Summary of the invention

[0005] The object of the present invention is to provide a phosphogypsum concrete and a preparation method thereof. By using phosphogypsum as a raw material, the phosphogypsum is pretreated to prepare a phosphogypsum light aggregate with high strength, good impermeability and strong chemical resistance. The light aggregate can replace natural river sand, and the prepared phosphogypsum concrete has high strength and good durability.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention is to provide a method for preparing phosphogypsum lightweight aggregate, comprising the following steps:

[0008] The pretreated phosphogypsum is mixed with a cementitious material and then ball-milled, then mixed with an alkali activator, a retarder and water, granulated, calcined after curing, crushed after cooling, and sieved to obtain phosphogypsum lightweight aggregate;

[0009] The pretreatment step of the phosphogypsum includes: first drying the phosphogypsum and then crushing it, and then calcining it to complete the pretreatment.

[0010] Since the composition of phosphogypsum is relatively complex and contains a large number of other impurity components in addition to calcium sulfate, the present invention first performs a calcination pretreatment on it to decompose the impurity components therein to improve the strength and durability of the lightweight aggregate prepared from the phosphogypsum.

[0011] Preferably, the ball milling time is 4 to 6 hours.

[0012] Preferably, in parts by weight, the pretreated phosphogypsum is 40 to 50 parts, the cementitious material is 25 to 35 parts, the alkali activator is 0.03 to 0.1 parts, the retarder is 0.01 to 0.03 parts, and the water is 20 to 30 parts.

[0013] Preferably, the cementitious materials are slag powder and fly ash, and the mass ratio of slag powder to fly ash is 2:1-2.

[0014] Preferably, the activator is quicklime, the particle size of which does not exceed 20 μm; and the retarder is wood sulfonate.

[0015] Preferably, the curing temperature is 25±2°C and the relative humidity is 80-90%; the heating program of the sintering treatment is to heat to 300-350°C at a heating rate of 4-5°C / min, keep warm for 1 hour, and then heat to 500-600°C at a heating rate of 8-10°C / min and keep warm for 2 hours.

[0016] The present invention effectively improves the density of phosphogypsum lightweight aggregate through a special sintering treatment method, thereby improving its strength, impermeability and chemical resistance.

[0017] Preferably, the drying temperature is 50-60° C., and the time is 12-24 hours; the calcination temperature is 200-300° C., and the time is 2-3 hours.

[0018] The second technical solution of the present invention is to provide a phosphogypsum lightweight aggregate prepared according to the above preparation method.

[0019] The third technical solution of the present invention is to provide a phosphogypsum concrete, which is prepared by using the above-mentioned phosphogypsum lightweight aggregate as aggregate and combining it with other concrete components.

[0020] The phosphogypsum lightweight aggregate prepared by the present invention can replace natural river sand as lightweight aggregate, and the prepared concrete is not inferior to the concrete prepared with natural river sand as raw material in terms of strength and durability.

[0021] The beneficial technical effects of the present invention are as follows:

[0022] The present invention provides a method for preparing concrete by using phosphogypsum waste as raw material, which can solve the problems of ecological environment damage, groundwater resource pollution and land resource waste caused by phosphogypsum accumulation to a certain extent.

[0023] When the phosphogypsum lightweight aggregate prepared with phosphogypsum as raw material is used to prepare phosphogypsum concrete, the prepared phosphogypsum concrete has high strength and good durability, and its performance is not inferior to that of concrete prepared with natural river sand as aggregate, indicating that the method provided by the present invention has great promotion and application value. DETAILED DESCRIPTION

[0024] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0025] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0026] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0027] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0028] Example 1

[0029] Preparation of phosphogypsum lightweight aggregate:

[0030] (1) drying the phosphogypsum at 60° C. for 12 h, then physically crushing it, transferring it to a rotary kiln and calcining it at 300° C. for 2 h, and cooling it to obtain pretreated phosphogypsum;

[0031] (2) taking 50 parts of the pretreated phosphogypsum in step (1), 20 parts of blast furnace slag powder and 10 parts of fly ash, adding them to a ball mill and ball milling for 4 hours, mixing the obtained powder with 0.05 parts of quicklime (particle size not exceeding 20 μm), 0.02 parts of lignosulfonate and 24 parts of water, granulating them with a disc granulator (particle size is about 0.5 cm), and curing them at 25±2° C. and a relative humidity of 80-90% for 24 hours to obtain phosphogypsum granules;

[0032] (3) The phosphogypsum granules obtained in step (2) are transferred to a rotary kiln, heated to 300° C. at a heating rate of 5° C. / min, kept warm for 1 h, and then heated to 600° C. at a heating rate of 10° C. / min, kept warm for 2 h, and naturally cooled. The fired phosphogypsum granules are physically crushed and sieved into particles with a size of 0.15 to 5 mm to obtain phosphogypsum lightweight aggregate.

[0033] According to the national standard GB / T17431.2 "GBT-17431.2-1998-Light Aggregate and Its Test Methods-Part 2 Light Aggregate Test Methods", the physical properties of the sintered phosphogypsum pellets of Example 1 were tested, and the measured bulk density was 1072 kg / m 3 , the cylinder pressure strength is 19.7MPa.

[0034] Comparative Example 1

[0035] Preparation of phosphogypsum lightweight aggregate:

[0036] Compared with Example 1, the only difference is that the calcination step in step (1) is omitted and the dried phosphogypsum is directly ball-milled.

[0037] According to the national standard GB / T17431.2 "GBT-17431.2-1998-Light Aggregate and Its Test Methods-Part 2 Light Aggregate Test Methods", the physical properties of the sintered phosphogypsum pellets of Comparative Example 1 were tested, and the measured bulk density was 976 kg / m 3 , the cylinder pressure strength is 14.7MPa.

[0038] Comparative Example 2

[0039] Preparation of phosphogypsum lightweight aggregate:

[0040] Compared with Example 1, the only difference is that the sintering temperature program in step (3) is adjusted to heat to 600° C. at a heating rate of 10° C. / min and keep warm for 3 h.

[0041] According to the national standard GB / T17431.2 "GBT-17431.2-1998-Light Aggregate and Its Test Methods-Part 2 Light Aggregate Test Methods", the physical properties of the sintered phosphogypsum pellets of Comparative Example 2 were tested, and the measured bulk density was 850kg / m 3 , the cylinder pressure strength is 13.6MPa.

[0042] It can be seen from the above results that the intermediate product of the phosphogypsum lightweight aggregate prepared by the present invention has high strength, which is better than conventional ceramsite (usually not more than 6MPa), and its bulk density is also less than that of crushed stone (usually 1300-1600kg / m 3). If the calcination pretreatment of phosphogypsum is omitted, although the bulk density of the intermediate product phosphogypsum pellets is reduced, the strength reduction is too large, and the prepared phosphogypsum pellets have more cracks, which is not conducive to the durability of the subsequent lightweight aggregate. After replacing the staged firing with the single temperature firing, the prepared phosphogypsum pellets have more pores, which is also not conducive to the durability of the subsequent lightweight aggregate.

[0043] Example 2

[0044] Preparation of phosphogypsum concrete:

[0045] The phosphogypsum lightweight aggregate prepared in Example 1 was used as aggregate, and the raw materials were prepared according to the weight proportions of 100 parts of 32.5 ordinary Portland cement, 115 parts of phosphogypsum lightweight aggregate (particle size 0.15-5 mm), 200 parts of crushed stone (particle size 10-20 mm), and 50 parts of water, and concrete test blocks were prepared according to the conventional method.

[0046] Comparative Example 3

[0047] Preparation of phosphogypsum concrete:

[0048] The phosphogypsum lightweight aggregate prepared in Comparative Example 1 was used as aggregate, and the raw materials were prepared according to the weight proportions of 100 parts of 32.5 ordinary Portland cement, 115 parts of phosphogypsum lightweight aggregate (particle size 0.15-5 mm), 200 parts of crushed stone (particle size 10-20 mm), and 50 parts of water, and concrete test blocks were made according to the conventional method.

[0049] Comparative Example 4

[0050] Preparation of phosphogypsum concrete:

[0051] The phosphogypsum lightweight aggregate prepared in Comparative Example 2 was used as aggregate, and the raw materials were prepared according to the weight proportions of 100 parts of 32.5 ordinary Portland cement, 115 parts of phosphogypsum lightweight aggregate (particle size 0.15-5 mm), 200 parts of crushed stone (particle size 10-20 mm), and 50 parts of water, and concrete test blocks were made according to the conventional method.

[0052] Comparative Example 5

[0053] Preparation of control concrete:

[0054] Prepare the raw materials according to the weight proportions of 100 parts of 32.5 ordinary Portland cement, 115 parts of natural river sand (particle size 0.15-5 mm), 200 parts of crushed stone (particle size 10-20 mm), and 50 parts of water, and make concrete test blocks according to the conventional method.

[0055] The 28d compressive strength of the concrete test blocks prepared in Example 2 and Comparative Examples 3-5 was measured according to GB / T 50081-2002 “Standard for Test Methods for Mechanical Properties of Ordinary Concrete”. The test results are shown in Table 1.

[0056] The concrete test blocks prepared in Example 2 and Comparative Examples 3-5 were immersed in water, and the weight gain percentage after 24 hours was used to represent the anti-seepage ability (weight gain percentage = weight after immersion / weight before immersion - 100%). The test results are shown in Table 1.

[0057] The 28d sulfate corrosion resistance coefficient of the concrete test blocks prepared in Example 2 and Comparative Examples 3-5 was measured according to GB / T 31289-2014 "Marine Portland Cement". The test results are shown in Table 1.

[0058] Table 1 Strength and durability of each group of concrete

[0059]

[0060] It can be seen from Table 1 that the compressive strength, impermeability and salt resistance of the prepared concrete by replacing natural river sand with the phosphogypsum lightweight aggregate prepared by the present invention are not inferior to those of the control concrete made of natural river sand. The preparation scheme of the present invention can solve the problems of low strength and durability of the current phosphogypsum concrete.

[0061] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing phosphogypsum lightweight aggregate, characterized in that: The following steps are involved: The pretreated phosphogypsum is mixed with a cementitious material and then ball-milled, then mixed with an alkali activator, a retarder and water, granulated, calcined after curing, crushed after cooling, and sieved to obtain phosphogypsum lightweight aggregate; The pretreatment step of the phosphogypsum includes: first drying the phosphogypsum and then crushing it, and then calcining it to complete the pretreatment; The curing temperature is 25±2°C and the relative humidity is 80-90%; the heating procedure of the sintering treatment is to heat to 300-350°C at a heating rate of 4-5°C / min, keep warm for 1 hour, then heat to 500-600°C at a heating rate of 8-10°C / min and keep warm for 2 hours.

2. The method for preparing phosphogypsum lightweight aggregate according to claim 1, characterized in that: The ball milling time is 4 to 6 hours.

3. The method for preparing phosphogypsum lightweight aggregate according to claim 1, characterized in that: In parts by weight, the pretreated phosphogypsum is 40 to 50 parts, the cementitious material is 25 to 35 parts, the alkali activator is 0.03 to 0.1 parts, the retarder is 0.01 to 0.03 parts, and the water is 20 to 30 parts.

4. The method for preparing phosphogypsum lightweight aggregate according to claim 1, characterized in that: The cementitious materials are slag powder and fly ash, and the mass ratio of slag powder to fly ash is 2:1-2.

5. The method for preparing phosphogypsum lightweight aggregate according to claim 1, characterized in that: The activator is quicklime, and its particle size does not exceed 20 μm; the retarder is wood sulfonate.

6. The method for preparing phosphogypsum lightweight aggregate according to claim 1, characterized in that: The drying temperature is 50-60° C., and the time is 12-24 hours; the calcination temperature is 200-300° C., and the time is 2-3 hours.

7. A phosphogypsum lightweight aggregate prepared according to the preparation method according to any one of claims 1 to 6.

8. A phosphogypsum concrete, characterized in that: The concrete is prepared by using the phosphogypsum lightweight aggregate described in claim 7 as aggregate and mixing it with other concrete components.

Citation Information

Patent Citations

  • Gypsum-based unfired aggregate

    CN113121138A

  • Phosphogypsum-based regenerated aggregate as well as preparation method and application thereof

    CN116283001A

  • High-strength anti-crack concrete and preparation method thereof

    CN118026626A